Is the obstructive uropathy a sequence of vascular disoders in BPH patients? - Gubar, A. O.; Bachurin, G. V.; Bachurin, V. I.; Dovbysh, M. A.; Ahmed, Rafia Hasan; Бачурін, Георгій Вікторович; Бачурін, Віктор Іванович; Довбиш, Михайло Афанасійович (Запорізький державний медичний університет, 2015)
Introduction & objectives: Benign prostate enlargement (BPE) and vascular diseases are both common in aging men. The aim of this study was to determine the role of concomitant vascular disorder in BPE progression and development of obstructive uropathy (OU).